Internal organizational dynamics survey : CARICOM - Rambachan, Surujrattan ([Caricom Secretariat] [Georgetown]GY, 1994)
Provides data that informs the development of a Human Resource Plan for the Secretariat. Examines the level of organizational competence. Assesses the organization's readiness for change and surveys staff perspectives.